2021
DOI: 10.26605/medvet-v15n2-4398
|View full text |Cite
|
Sign up to set email alerts
|

Parasites in vegetables used for human consumption: a risk for public health

Abstract: Vegetables are pivotal food source to the human beings, representing the source of key nutrients, which in turn the occurrence of chronic diseases. Nonetheless, the consumption of poorly washed or in nature vegetables may expose individuals to the risk of infection by parasites. The aim of this study was to assess the contamination by parasites of medical and veterinary concern in raw vegetables used for human consumption. Fresh vegetables [i.e., lettuces (n = 50), carrots (n = 50) and beet (n = 50)] were acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Among the types of samples surveyed, it is interesting to observe the predilection for leafy vegetables in the analyses, such as lettuce, parsley, and spinach (Fig 2). This fact may be explained by prevalence studies, which revealed that lettuce is the vegetable with the highest contamination [16][17][18][19][20], and this probably influences the choice of this type of vegetable in the analyzes.…”
Section: Discussionmentioning
confidence: 99%
“…Among the types of samples surveyed, it is interesting to observe the predilection for leafy vegetables in the analyses, such as lettuce, parsley, and spinach (Fig 2). This fact may be explained by prevalence studies, which revealed that lettuce is the vegetable with the highest contamination [16][17][18][19][20], and this probably influences the choice of this type of vegetable in the analyzes.…”
Section: Discussionmentioning
confidence: 99%